New Avenues to Design Toxoplasma Vaccines Based on Oocysts and Cysts - Arranz-Solís, David; Saeij, Jeroen P. J. (Frontiers in Immunology, 2022)
Toxoplasmosis is a worldwide disease affecting all warm-blooded animals, including humans. Vaccination strategies aimed at inducing an efficient immune response while preventing transmission have been attempted in the past. While many different approaches can partially protect immunized animals against subsequent infections, full and lasting protection is rarely attained and only with live-attenuated vaccines. In addition, vaccines based on mutant strains that are deficient in forming the chronic phase of the parasite (such as Toxovax™) cannot be extensively used due to their zoonotic potential and the possibility of reversion to virulent phenotypes. An increasing number of studies using emerging genetic-engineering tools have been conducted to design novel vaccines based on recombinant proteins, DNA or delivery systems such as nanoparticles. However, these are usually less efficient due to their antigenic simplicity. In this perspective article we discuss potential target genes and novel strategies to generate live-attenuated long-lasting vaccines based on tissue cysts and oocysts, which are the environmentally resistant chronic forms of Toxoplasma. By selectively disrupting genes important for parasite dissemination, cyst formation and/or sporozoite invasion, alone or in combination, a vaccine based on a live-attenuated strain that elicits a protective immune response while preventing the transmission of Toxoplasma could be created. Finally, further improvements of protocols to generate Toxoplasma sexual stages in vitro might lead to the production of oocysts from such a strain without the need for using mice or cats.